Calcium oxide-based catalysts for conventional and supercritical water gasification of palm fruit bunches in hydrogen production - Seenivasagam, Sivasangar (2015)
Hydrogen shows great potential as a clean and alternative energy resource that could reduce the dependency of fossil fuel consumption.Commercially,hydrogen is produced from natural gas reforming and coal gasification.Apart from this,biomass conversion via gasification method is regarded as a promising technique for hydrogen production.Empty palm fruit bunches (EFB) are considered as an abundant biomass wastewhich is apotential feedstock for gasification process. In this investigation,catalytic EFB conversion into hydrogen were studied in two different prominentgasification methodsthatincludes conventional (900ºC in partial O2 environment) and supercritical water gasificationreaction (380 ºC). Hence, a series ofCaO based catalysts were synthesized via wet impregnation method using bulk CaO as a base added with primary (Ni) and secondary (La, Mg, Ba, Nd, Na, K, Zn, Co and Fe) dopants.The prepared catalysts were characterized by x-ray diffraction (XRD), N2 adsorption-desorption (BET), thermal gravimetric analysis (TGA), temperature programmed reduction (TPR-H2)and temperature programmed desorption(TPD-CO2). Furthermore,the effects of catalyst in EFB conversion to hydrogen were tested in both gasification techniques. Preliminary catalytic studies show thatBaO doped NiO-CaO catalyst was found to be very active in conventional gasification while ZnO doped NiO-CaO catalysts in supercritical water gasification reaction (SCWG). Both catalysts exhibit high selectivity towards hydrogen production. This is due to improvements in catalytic activity ofNiO-CaO with additions of BaO or ZnO dopants that enhances gasification of EFB and promote hydrogen favored reactions. In comparison with both techniques SCWG reaction shows several advantages over conventional gasification such as lower reaction temperature, higher hydrogen yield, tolerate high moisture content feedstock (EFB), reduce tar production and shorter reaction time. Therefore, SCWG reactionwas selected for EFB conversion using ZnO doped NiO-CaO catalysts with both unreduced and reduced catalysts.The catalytic results of reduced ZnO/Ni-CaO catalyst showsignificant improvement in terms of hydrogen selectivity. Formation of Ni.8Zn.2O solid solution phase on the CaOsurface was found to be the active in catalyzing water gas shift reaction while the presence of metallic Ni promotescarbon gasification and reforming reactions. The highest hydrogen concentration (105.7 mmol mL-1)was observedwith 5wt.%ZnO doped 5wt% Ni-CaO catalyst and found to be increased with increasing reaction time.Further, Ni and ZnO loading were increased in catalyst formulationeven though concentration of hydrogen didn’t displayed any significant difference. This is due to the possible particle agglomerations on the CaO surface.However, only slight improvement in carbon gasification is observed with 8 wt.% of Ni loading. Therefore,based on the information obtained Ni loading in the range of 5-8 wt.% with 5wt.% of ZnO on CaO was predicted as an optimum catalyst formulations that provide high catalytic activity and selectivity towards hydrogen production.